Jordanian Patients’ Perspectives of the Role of Complementary Medicine in the Treatment of Cancer - Suha Omran; Husam Barakat (Jordan Journal of Nursing Research, 2023)
Background: Cancer is considered one of the most significant health issues in Jordan. The use of Traditional, Complementary, and Integrative medicine (TCI) as a complementary approach to treating cancer patients can serve to alleviate symptoms, which ultimately enhances the quality of life. Jordanians have a positive attitude towards complementary medicine (CM). Currently, hospitals in Jordan offer no or limited CM services as part of oncology or palliative cancer care. Objective: The aim of this study was to explore the perspectives of Jordanian cancer patients regarding the use of CM and its integration in hospitals. Methods: In this descriptive study, 253 patients formed a convenient sample, and they were asked to complete the Questionnaire on Integrating Complementary Medicine in Oncology Treatment. Results: More than 40% of the patients were found to have used CM during chemo or radiotherapy. Different types of herbal medicine were the most used treatments. More than half of the participants showed willingness to consult with care providers on how to use CM for cancer treatment if it was integrated into their oncology treatment. Participants expected CM to improve their symptoms of pain, nausea and vomiting, and changes in appetite. Conclusions: Due to the concerns about applying these approaches, it is necessary to train care providers to consider the perspective of cancer patients in integrating evidence-based culturally sensitive consultation. Implications to Nursing: Further research is needed to explore the perspectives of healthcare providers and care givers on CM use and its usefulness alongside the conventional medical treatment.